On hyperbolic heat conduction - Frischmuth, K.; Cimmelli, V.A. (Archives of Mechanics, 1997)
In a previous paper [5], numerical solutions of initial-boundary value problems for the semi-empirical model of heat conduction were compared with available experimental results. In [6] the model was modified by introducing more realistic approximations of the constitutive functions, basing on measured specific heat, heat conductivities and second sound speeds for NaF at low temperatures (10 ... 20° K). In the present paper we suggest a method to choose the free parameters entering the constitutive functions by minimizing an error functional, measuring the differences between the theoretical and experimental heat pulses.